Analisis Pengaruh Faktor Psikologis Terhadap Keputusan Pembelian Produk Kecantikan - Muhammad Arkan, Fauzan; , Kussudiyarsana S.E., M.Si (2017)
This study aimed to analyze the influence of psychological factors on purchase decisions beauty products at the Faculty of Economics and Business, University of Muhammadiyah Surakarta. This type of research is a comparative study. The population in this study were students of the Faculty of Economics and Business UMS. The sample in this study was 100 students make up's and / or skin care user at UMS FEB. Sampling by convenience sampling. Data used in the form of primary and secondary data. The data collection technique using questionnaires. Data were analyzed using the validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, F, R2 test. The results showed that: Motivation positive and significant effect on purchasing decisions beauty products based on the value of t, t> t table (5.254> 1.985); Perception positive and significant impact on purchasing decisions beauty products based on the value of t, thitung> t table (2.619> 1.985); Motivation and Perception jointly influence the purchasing decisions of beauty products, evidenced by F. Test on the F test obtained F count equal to 27.458 and F table 3.090 (H0, H1 accepted); Results of testing the coefficient of determination (R2) shows that the perceptions and motivations are able to explain the variability of 54.7%. and the mean score of the questionnaire purchasing beauty products are more influenced by emotional rather than rational motives (3,257 appeals 4,088) Keywords: Purchasing Decisions, Motivation, Perception